Little evidence of bone marrow-derived hepatocytes in the replacement of injured liver - Kanazawa, Yoshiyuki (National Academy of Sciences, 2003)
We have tested the ability of bone marrow (BM) cells (BMCs) to form hepatocytes in liver injury models. We used three models: (i) carbon tetrachloride (CCl(4)) treatment, (ii) albumin-urokinase transgenic mouse [TgN(Alb1Plau)], and (iii) hepatitis B transgenic mouse [TgN(Alb1HBV)]. As a nonselective liver injury model, irradiated C57BL/6 (B6) mice were transplanted with BMCs from GFP transgenic mouse [TgN(ActbEGFP)] or β-galactosidase transgenic mouse [TgN(MtnLacZ)] followed by the administration of CCl(4). Irradiated TgN(Alb1HBV) and TgN(Alb1Plau) were also transplanted with BMCs from TgN(ActbEGFP) or TgN(MtnLacZ). Approximately 1.5 × 10(6) hepatocytes per liver were analyzed for GFP-positive cells, and the whole livers were inspected for β-galactosidase expression. No GFP-positive hepatocytes and no gross blue staining of the livers with 5-bromo-4-chloro-3-indolyl β-d-galactoside in any of the 18 recipient mice analyzed were detected. The livers from female animals with gender-mismatched BM transplantation were also tested with Y chromosome fluorescent in situ hybridization analysis to detect donor-derived cells. A total of five isolated hepatocytes were positive for Y chromosome in 4.1 × 10(5) hepatocytes analyzed. Our results demonstrate that there is little or no contribution of BMCs to the replacement of injured livers in these models. We conclude that BM-derived cells cannot generally lead to a cure of liver damage.